Variance of collapse capacity of SDOF systems under earthquake excitations. - Ibarra, Luis (Earthquake engineering & structural dynamics.)
The variance of collapse capacity is an important constituent of probabilistic methodologies used to evaluate the probability of collapse of structures subjected to earthquake ground motions. This study evaluates the effect of ground motion randomness (i.e. record to record (RTR) variability) and uncertainty in the deterioration parameters of single degree of freedom (SDOF) systems on the variance of collapse capacity. Collapse capacity is evaluated in terms of a relative intensity defined as the ratio of ground motion intensity to a structure strength parameter. The effect of RTR variability on the variance of collapse capacity is directly obtained by performing dynamic analyses of deteriorating hysteretic models for a set of representative ground motions. The first order second moment (FOSM) method is used to quantify the effect of deterioration parameter uncertainty. In addition to RTR variability, the results indicate that uncertainty in the displacement at the peak (cap) strength and the post-capping stiffness significantly contribute to the variance of collapse capacity. If large dispersion of these parameters exists, the effect of uncertainty in deterioration parameters on the variance of collapse capacity may be comparable to that caused by RTR variability.